2012
DOI: 10.1002/mus.22303
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment enhances the functional recovery of sciatic nerves after transection and repair

Abstract: GH enhanced the functional recovery of the damaged nerves, thus supporting the use of GH treatment, alone or combined with other therapeutic approaches, in promoting nerve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 50 publications
4
25
1
Order By: Relevance
“…Latency is considered as a major indicator of myelination 19 ; however, in our study there was no significant increase in latency values after injury. Previous studies have shown that latency increased at an early phase after nerve injury, followed by a decrease in groups that received therapy 20,21 ; however, in our study, there was no significant difference in latency values between the IG and the SG. There are studies reporting similar results in the literature.…”
Section: Discussioncontrasting
confidence: 97%
“…Latency is considered as a major indicator of myelination 19 ; however, in our study there was no significant increase in latency values after injury. Previous studies have shown that latency increased at an early phase after nerve injury, followed by a decrease in groups that received therapy 20,21 ; however, in our study, there was no significant difference in latency values between the IG and the SG. There are studies reporting similar results in the literature.…”
Section: Discussioncontrasting
confidence: 97%
“…We also demonstrated, in rats, that the administration of GH administration led to complete functional recovery of the sciatic nerves after their transection [92], promoting the appearance of a high number of axons and Schwann cells, while in the group of rats treated with placebo, a persistent paralysis of the affected limb was present. (1) The patient at admission was unable to move the tongue, it was atrophic, and the mouth continuously accumulated highly dense mucous saliva (sympathetic saliva).…”
Section: Ghd and Nervous System Functioningmentioning
confidence: 61%
“…It was stated that GH, next to the promotion of the proliferative activity, shows the ability to inhibit apoptosis (Kölle et al, 2003;Bogazzi et al, 2004). The growth hormone also has a great meaning in the regeneration of nervous fibres and in wound healing (Breederveld, Tuinebreijer, 2012;Devesa et al, 2012). GH stimulates migration and proliferation of neural stem cell (NSC), as well as induction of differentiation of progenitor nervous cells (Pathipati et al, 2011).…”
Section: Hormone Of Growth Only?mentioning
confidence: 99%